Study of Ichthyofauna: Fishes in the Enipeas River's Catchment Area, Central Macedonia, Greece - Fytilis, Konstantinos; Palatos, Evangelos (Journal of Sustainability and Environmental Management, 2022)
The management of water resources and the achievement of the Water Framework Directive 2000/60 / EC's objectives were the key research themes for this study. The study of Ichthyofauna was conducted at nine areas of Enipeas river basin in central Macedonia region of Greece. At the sampling stations, the electrofishing method was applied. The physicochemical parameters at the sampling site were measured with a multiparametric HANNA water quality meter, while water samples were collected and transferred to laboratories of the Biology Department of the Aristotle University of Thessaloniki for analysis of nutrients and major ions. Out of nine stations, only one station discovered fish. Because the sampling was only done once, it is suggested that it be repeated at a different time because the research location is located in one of Greece's major catchments. Only three fish species were identified in the entire catchment area, indicating that more detailed studies are needed covering different surrounding areas.